31.2: Low Dielectric Constant Materials for High Performance LCDs. Issue 1 (June 2015) - Chen, Haiwei; Peng, Fenglin; Wu, Shin‐Tson; Hu, Minggang; Li, Jian; An, Zhongwei; Li, Ming‐Chun; Lee, Seok‐Lyul; Tsai, Weng‐Ching
Abstract : A small |Δε| LC mixture exhibits an ultra‐low viscosity, low activation energy, and high transmittance yet at a reasonably low voltage. Its response time remains 42 ms even at −20°C. These materials are attractive for fringing field switching‐based mobile displays, IPS‐based 4K2K TVs, and MTN‐based wearable LCoS projection displays.